2017
DOI: 10.1038/nature21409
|View full text |Cite
|
Sign up to set email alerts
|

Class IIa HDAC inhibition reduces breast tumours and metastases through anti-tumour macrophages

Abstract: Although the main focus of immuno-oncology has been manipulating the adaptive immune system, harnessing both the innate and adaptive arms of the immune system might produce superior tumour reduction and elimination. Tumour-associated macrophages often have net pro-tumour effects, but their embedded location and their untapped potential provide impetus to discover strategies to turn them against tumours. Strategies that deplete (anti-CSF-1 antibodies and CSF-1R inhibition) or stimulate (agonistic anti-CD40 or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
369
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(405 citation statements)
references
References 34 publications
15
369
0
Order By: Relevance
“…In the paper by Guerriero et al [8] a new approach to reprogram monocytes and macrophages into tumoricidal cells is described using TMP195, a new Class IIa Histone Acetyl Deacetylase (HDAC) inhibitors. HDACs are part of the enzymatic machinery that modifies chromatin [9] by histone de-acetylation thus changing the cell's transcriptional profile.…”
mentioning
confidence: 99%
“…In the paper by Guerriero et al [8] a new approach to reprogram monocytes and macrophages into tumoricidal cells is described using TMP195, a new Class IIa Histone Acetyl Deacetylase (HDAC) inhibitors. HDACs are part of the enzymatic machinery that modifies chromatin [9] by histone de-acetylation thus changing the cell's transcriptional profile.…”
mentioning
confidence: 99%
“…3 An alternative approach to replace macrophage depletion strategies could be based on the fact that tumor-associated macrophages preserve their plasticity, which provides therapeutic potential to re-program them from tumor-promoting cells to cells with tumoricidal activities. In a recent study, Guerriero et al 4 provided further data supporting the notion that rendering tumor-associated macrophages to display anti-tumorigenic activities may be beneficial. Until recently, the therapeutic potential of class IIa histone deacetylases (HDAC) (for example, HDAC4, HDAC5, HDAC7 and HDAC9) was impaired by the lack of potent and selective compounds that can antagonize their function.…”
mentioning
confidence: 69%
“…These results provided the rationale to test the hypothesis that class IIa HDAC inhibition will promote an anti-tumor innate immune response. To this end, Guerriero et al 4 used TMP195 in vivo using a macrophage-dependent mouse model, namely, the MMTV-PyMT mammary carcinoma. 6 Tumor-bearing mice treated with TMP195 displayed increased levels of CD11b+ myeloid cells, specifically in macrophages.…”
mentioning
confidence: 99%
“…It has also been shown that a class IIa histone deacetylase (HDAC) inhibitor, TMP195, can stimulate macrophages to have an anti-tumor phenotype. This inhibitor reduces tumor burden and pulmonary metastases in a macrophage-dependent mouse model of breast cancer [65].…”
Section: Inflammation and Immune Cellsmentioning
confidence: 99%